Pati Jinich treasures of the Mexican table : classic recipes, local secrets - Jinich, Pati (Houghton Mifflin Harcourt, 2021)
"The "buoyant and brainy Mexican cooking authority" (New York Times) and star of the three-time James Beard Award-winning PBS series Pati's Mexican Table brings together more than 150 iconic dishes that define the country's cuisine Although many of us can rattle off our favorite authentic Mexican dishes, we might be hard pressed to name more than ten. Which is preposterous, given that Mexico has a rich culinary history stretching back thousands of years. For her newest book, Pati Jinich brings home the signature recipes that home cooks, market vendors, and chefs have shared with her as she crisscrossed her native country for the past decade. From Baja lobster tacos to Oaxacan-style grilled flank steak, these recipes represent the culinary diversity of the nation that has, depending on how you count them, as many as thirty-two different cuisines. Each recipe is a classic. Each one comes with a story told in Pati's warm, relatable style. And each has been tested in Pati's American kitchen to ensure it is the best of its kind. "--